USING INNOVATIVE TECHNOLOGIES IN TEACHING AND LEARNING LANGUAGE - Tuychiyeva Parvina Baxodirovna (Galaxy International Interdisciplinary Research Journal, 2022)
This article is about teaching and learning languages with the help of computer, multimedia assistance. From this article, you come across about virtual resource and their implementation to teaching process. In this article shows about internet learning, CALL and MALL science and teaching models.